1989
DOI: 10.2527/jas1989.673779x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elevated Ambient Temperatures on Puberty in Gilts

Abstract: Effects of elevated ambient temperature on puberty and related physiological responses were studied in 40 gilts. Group 1 (n = 20) gilts were born in September and Group 2 (n = 20) gilts were born in March. Gilts were placed in environmentally controlled chambers at 140 d of age. After a 10-d acclimation period at 20 degrees C, 35% relative humidity (RH), and 12 h light (L)/12 h dark (D), gilts within each group were randomly assigned to one of two treatments: control (C; 15.6 degrees C, 35% RH, 12 h L/12 h D) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
8

Year Published

1990
1990
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 20 publications
2
24
0
8
Order By: Relevance
“…Hot and humid summer climate causes heat stress reducing reproductive performance and longevity of sows [21,22]. Studies showed that heat stress diminished the secretion of FSH and LH, and delayed puberty in gilts [18,21].…”
Section: Introductionmentioning
confidence: 99%
“…Hot and humid summer climate causes heat stress reducing reproductive performance and longevity of sows [21,22]. Studies showed that heat stress diminished the secretion of FSH and LH, and delayed puberty in gilts [18,21].…”
Section: Introductionmentioning
confidence: 99%
“…Para as matrizes suínas a temperatura ambiente considerada de conforto varia entre 7 e 23 °C (Noblet et al, 1989;Lucas & Cruz, 1997); entretanto, altas temperaturas no interior das instalações influenciam negativamente a eficiência reprodutiva, com redução da fertilidade (Peltoniemi et al, 1999), em especial em fêmeas primíparas, além de atraso da maturidade sexual (Flores et al, 1989;Perez & Gutierez, 1987) e maior mobilização de gordura corporal durante a lactação (Barb et al, 1991).…”
Section: Introductionunclassified
“…Thus, in addition to PP it appears that high temperature is seasonal environment factor that can delay puberty in gilts. A previous study has suggested that the effect of elevated temperatures on delayed puberty is due to one or both of the following factors; reduced concentrations of gonadotropins and decreased responsiveness of the ovary to gonadotropins (Flowers et al, 1989). Fig.…”
Section: Discussionmentioning
confidence: 97%